Investigation of the HA film deposited on the porous Ti6Al4V alloy prepared via additive manufacturing; IOP Conference Series: Materials Science and Engineering; Vol. 98 : Interdisciplinary Problems of Nanotechnology, Biomedicine and Nanotoxicology (Nanobiotech 2015) - Surmeneva M. A. Maria Alexandrovna; Chudinova E. A. Ekaterina Aleksandrovna; Syrtanov M. S. Maksim Sergeevich; Koptioug A.; Surmenev R. A. Roman Anatolievich (2015, 2015)
Title screen